Voting in the echo chamber?: Patterns of political online activities and voting behavior in Switzerland - Ackermann, Kathrin; Stadelmann-Steffen, Isabelle (Swiss political science review, 2022)
Understanding the political consequences of digitalization is among the key challenges for modern societies. A pressing issue is the question whether political online activities make individuals more close-minded and less willing to consider alternative arguments. We examine this question using a peculiarity of the Swiss electoral system - the possibility to split votes - as a behavioral outcome measure. We argue that political online activities might either make individuals less likely to split votes (“echo chamber”-argument) or more likely to spread their votes across parties (“deliberation”-argument). Empirically, we use data from the Swiss Election Study Selects 2019 to test these arguments. The results of a hierarchical logistic regression analysis do not support any of the conflicting arguments. Yet, additional analyses suggest that political interest moderates the relationship between online activities and vote splitting: political interest makes online activists more likely to split votes.
Gesehen am 02.02.2022